portrait of the architect Vladimir Bukh (1935-2013) - Grigoryeva, Elena (project baikal, 2014)
Bukh, the maximalist, as some of his friends called him. Then a more appropriate word was found – perfectionist. He aimed at perfection in everything he did. Be it town planning, municipal administration, work for a non-governmental organization Union of Architects of Russia, or creating a journal. The headwater area has always been and remains the best residential area ever built in recent history of Irkutsk. Irkutsk has never seen such a clever and honest chief architect. He has done so much to develop the city in the right and progressive direction and to promote high quality architecture. Andrei Bokov’s words can be related to Vladimir Bukh’s activity: “Everything that excites a fair and natural envy, the best examples of the second heroic epoch of the Russian-Soviet architecture, belong to Irkutsk architecture of the 1970s: orientation towards the future (but not the past), bigness of volumes and ideas, restraint, strictness, honesty, courage, persistency and strength. Irkutsk experience… was accumulated by young people, who were energetic, ambitious, lucky, captivating, talented and highly professional.” For several decades Bukh was a member of the Board of the Irkutsk organization of the Union of Architects of the USSR and then of Russia. The expression “to work with feeling” can be fully applied to Bukh. To do your job the right way. To do it according to your conscience. When he quitted the Board after demolition of the House on the Legs, it became clear that he was indispensable. He took to heart all town planning mistakes of the 1990s and 2000s. Pavlov’s death, demolition of the House on the Legs, legal proceedings, Nina’s death left scars on his heart. His daughter Lesya, grandchildren Nikita and Nastya, and great grandson Matvey are continuation of his life. All we, his colleagues and friends, can do is try to keep to his understanding of what is right and what is wrong. And to keep memory of a wonderful man. I do not know how long Project Baikal will exist (Bukh is one of the founders, the first and the best editor-in-chief), but all our further issues will be dedicated to him. As well as our defeats, since he did not hesitate to attempt tasks that were doomed to be defeated in the current system, in the current Order of Things in the town planning policy. In the book PAVLOV (together with Bukh, we had managed to compose it last summer, and in the beginning of September it came out in TATLIN publishing house in Yekaterinburg) there is a reference to the Strugatsky brothers that can be also applied to Bukh: “Like Saul, he fired at the Order of Things, knowing that it was useless”.